Peningkatan Kesejahteraan Masyarakat dan Izin Usaha Pengelolaan Hutan Kemasyarakatan (IUPHKm) di Pekon Air Naningan, Kabupaten Tanggamus - Prayudha Ananta (TECHNOBIZ : International Journal of Business, 2019)
Provision of IUPHKm by the Ministry of Environment and Forestry (KLHK) is to improve the people’s economy. Social forestry which was once illegally managed by the people, has now been legalized by the government through the KLHK. This study aims to find out how the impact of the provision of IUPHKm on farmer welfare in Air Naningan Village, Tanggamus Regency. The method used is an exploratory and descriptive method. The analysis used is crosstabulation. The results of this study were that after farmers in Air Naningan Village obtaining IUPHKm, their economy is increasesing as indicatet by : (1) their income increased by an average of 142.73 percent; (2) they are able to buy 1 to 3 units of motorcycles; (3) they have a permanent house.